A prospective cohort study of health outcomes following whiplash associated disorders in an Australian population. Issue 2 (3rd April 2006) - Rebbeck, T; Sindhusake, D; Cameron, I D; Rubin, G; Feyer, A-M; Walsh, J; Gold, M; Schofield, W N
Abstract : Objective: To define health outcomes of whiplash associated disorders (WAD) at three months, six months, and two years after injury and to examine predictors of these outcomes. Design: Prospective cohort study. Setting: New South Wales, Australia. Subjects: People with compensable motor crash injuries who reported whiplash as one of their injuries. Interventions: None. Main outcome measures: Functional Rating Index (FRI), Short Form 36 (SF-36) at three months, six months, and two years after injury, ascertained by telephone interview. Results: At three months, 33.6% of the cohort was recovered (as defined by FRI⩽25), increasing marginally at six months (38.9% recovered), but more significantly at two years (51.7% recovered, p = 0.001). The mean physical component score of the SF-36 improved at each time point (p = 0.002), while the mean mental component score did not (p = 0.59). Predictors of recovery at two years (as defined by global perceived effect) included a lower FRI index at baseline (p = 0.001) and closure of the claim at two years (p = 0.02). Conclusion: Whiplash injury had a large effect on the health of this Australian cohort of whiplash sufferers, with only 50% of the cohort recovered at two years. Physical measures of health appear to improve over time, whereas mental measures of health did not. Despite this, this cohort is largely able to participate in activities and work at two years. Prevention of chronic disability may lie with concentration of resources to those who score highly on the FRI at baseline. In addition, chronic psychological ill health may be prevented by directing treatment to those with poor scores on sensitive measures of psychological ill health at baseline.